A comparison of native starch, oxidized starch and CMC as copper-activated pyrite depressants. (1st September 2020) - Fletcher, Brenton; Chimonyo, Wonder; Peng, Yongjun
Highlights: Mild oxidation of starch improves its Cu-activated pyrite depressant performance. Improvement is due to scissioned polymer chains produced by starch oxidation. Performance of oxidized starch relative to CMC improves with concentration. Large molecules in oxidized starch contribute to performance at high concentrations. Abstract: The performance of native wheat starch (NWS), a hydrogen peroxide-oxidized wheat starch (Perox 3/30) and carboxymethyl cellulose (CMC) as copper-activated pyrite depressants are compared in lab-scale flotation trials. Both Perox 3/30 and CMC demonstrate similar and significantly better performance than NWS at dosages 100–300 g/t. At 700 g/t, both starches depressed essentially all of the copper-activated pyrite, whereas there was little change in recovery for CMC dosages above 300 g/t. The improved performance of Perox 3/30 and CMC at lower dosages appears to be associated with the presence of polymer structures with a hydrodynamic radius, Rh, of approximately 12–15 nm that are able to form a layer on the pyrite surface that is effective in preventing collector interaction. The continual decrease of flotation recovery with increasing NWS and Perox 3/30 dosage is likely associated with the greater molecular size of the starch polymers in that more hydroxyls can be associated with each adsorption site. The presence of branches on the starches that can extend from the pyrite surface plane may also improve interaction with the water phase near the surface, increase hydrophilicity and hence improve depression. Overall, the conformation of supramolecular and molecular structures of the polymers investigated here appear to be more influential than functional groups for depressing copper-activated pyrite.